Case Studies in Tax Revenue Mobilization in Low-Income Countries - Akitoby, Bernardin; Honda, Jiro.; Miyamoto, Hiroaki; Primus, Keyra (Washington, D.C. : International Monetary Fund, 2019)
How can Low-Income Countries (LICs) enhance tax revenue collection to finance their vast development needs? We address this question by analyzing seven tax reform experiences in LICs (Burkina Faso, The Gambia, Maldives, Mauritania, Rwanda, Senegal, and Uganda). Three lessons stand out, although reforms must be tailored to individual circumstances: (i) Tax reforms require first and foremost political commitment and buy-in from key stakeholders; (ii) Countries that pursue both revenue administration and tax policy reforms tend to see much larger and persistent gains; and (iii) A successful strategy often starts with fiscal reform measures with immediate effect to build momentum. These can include: simplifying the tax system; curbing exemptions; reforming indirect taxes on goods and services (e.g., excises); and better managing compliance risks through strengthening taxpayer segmentation (often beginning with strengthening the Large Taxpayers Office). A comprehensive reform strategy (e.g., a medium-term revenue strategy) can help to properly sequence reform measures and facilitate their implementation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet